184k views
6 votes
12x+y=−4 y=2x+16 im really confused on how to do this, i need to find the solution

User JuanN
by
4.1k points

2 Answers

4 votes

Answer:

(x, y) = (-10/7, 92/7)

Explanation:

12x + y = -4

y = 2x +16.

Substituting the value of y ( second equation ) into the first equation, we get:

12x + (2x + 16) = -4

14x + 16 = -4

14x = -20

x = -20/14 = -10/7.

Now, to find y, all we have to do is to substitute the value of x into the second eqation. We get:

y = 2 * (-10/7) + 16

y = -20/7 + 16

y = 92/7

User Zoonosis
by
4.8k points
10 votes

Answer:

here

Explanation:

12x+y=−4 y=2x+16 im really confused on how to do this, i need to find the solution-example-1
User Yingch Xue
by
5.3k points